P146 Establishing a sexual health research practice network in the North East. (18th May 2015) - Foster, Kirsty; Sullivan, Claire; Cheetham, Mandy; Shucksmith, Janet; McNall, Anne; Wilson, Lynn; Duncan, Sarah
Abstract : Background/introduction: There is a strong tradition of collaborative research and practice in sexual health in the North East of England. Aim(s)/objectives: The North East Sexual Health Research Practice Network brings together colleagues from academia, public health and clinical practice to share research findings and identify research questions based on local issues. Methods: A project group with representatives from local universities, Public Health England and local authorities developed a proposal for a regional sexual health research network to promote collaboration and share evidence of what works. A steering group was established to develop an initial work plan for the network. Results: The network has identified key outputs for its first year –including a website hosted by FUSE (the Centre for Translational Research in Public Health, a collaboration between the five North East universities), a mapping exercise of existing sexual health research in the region and an inaugural Research Practice event to share key findings and plan future projects. Discussion/conclusion: We have identified an enthusiasm for sexual health research in the region, and hope that the network will draw together colleagues working in different fields who may not be aware of the range of work being carried out across the region. We hope that by identifying research questions that are locally meaningful, and by offering support from colleagues with expertise in the field, we will generate research that will inform sexual health practice and commissioning, reduce duplication and ultimately improve the sexual health of people in the North East and beyond.